The Implementation of Top-Down Approach Method on Redesign of LAN Harvani Hotel Palembang - Rasmila Rasmila; Tri Ginanjar Laksana (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2019)
In this research, the object was taken from one of the hotels in Palembang, namely Harvani Hotel Palembang. This hotel is one of the hotels in South Sumatra Province, where this hotel has 4 floors. Harvani Hotel Palembang has a Local Area Network (LAN) which consists of several computers. LAN is very important to be applied to Harvani Hotel Palembang in order to support administrative work processes (management of hotel data, employee data, guest data to financial data) and guest needs (internet usage in every room of the Hotel which is one of the services provided by Harvani Hotel Palembang). However, the LAN owned by the Harvani Hotel Palembang still has disadvantages, such as LAN still cannot reach every hotel room on the 2nd floor. In addition, the administration side also faces obstacles because each floor of the Harvani Hotel Palembang has its own administrative section and then at the end of each work shift, reports from each administrative section are submitted to the administrative department on the 1st floor using external storage media. Therefore, it is necessary to redesign the Harvani Hotel Palembang LAN by applying the Top-Down Approach Method. The results of LAN redesign in this research will be displayed using Cisco Packet Tracer simulator software, where from the simulation results it can be seen that the new design of the Harvani LAN Hotel Palembang has connected the entire computer of each room and every floor of the Hotel. Therefore, if the results of this simulation are applied to Harvani Hotel Palembang, then the administrative work process can be managed directly because all data has been stored on the database server. In addition, this new LAN design has also reached all guest rooms of Harvani Hotel Palembang, so guests can access the internet in their respective rooms more comfortable.